Antropologi Hukum - Koentjaraningrat Koentjaraningrat (Antropologi Indonesia, 1989)
In describing the development of legal anthropology as a new subdiscipline in anthropology, the author firstly clarifies the differences between legal anthropology and the common law science. Although the description of law had been found in ethnographic literatures since two centuries ago, a particular analysis on law emerged in 1920s as the result of debates between Malinowski and R. Brown on the mechanism of social control in stateless societies. Problems of whether law exists in the state or stateless societies stimulated the anthropologists to define the boundaries and scopes of "law", such as L. Pospisil's definition. The development of studies, analysis, and interpretation on law systems in various societies lead to the emergence of legal anthropology as a subdiscipline in anthropology.